Effects of Loperamide on Mechanical Allodynia Induced by Herpes Simplex Virus Type-1 in Mice - Atsushi Sasaki; Yasutaka Nakashima; Ichiro Takasaki; Tsugunobu Andoh; Kimiyasu Shiraki; Yasushi Kuraishi (Elsevier, 2007)
In the present study, we investigated whether the peripherally acting µ-opioid receptor agonist loperamide would inhibit allodynia in the non-inflamed dermatome of mice with herpetic pain. Subcutaneous (s.c.) injection of loperamide (1 and 3 mg/kg) inhibited allodynia. Local (intraplantar) injection of loperamide (1 and 5 µg/site) also produced an anti-allodynic effect. The peripheral opioid receptor antagonist naloxone methiodide (0.1 mg/kg, s.c.) and the µ-opioid receptor-selective antagonist β-funaltrexamine (40 nmol/site, intraplantar and 20 mg /kg, s.c.) antagonized the anti-allodynic effects of systemic and local loperamide. Local injection of loperamide into the contralateral hind paw was without effect, suggesting that the effect is mediated through local action, not systemic action. Acute and subacute tolerance did not develop to the anti-allodynic effect of loperamide. In addition, there were no cross-tolerance between local opioids (morphine and loperamide) and systemic morphine. These results suggest that stimulation of peripheral µ-opioid receptors suppresses herpetic allodynia without tolerance development. The non-narcotic µ-opioid receptor agonist loperamide may relieve acute herpetic pain in patients with herpes zoster. Keywords:: acute herpetic pain, allodynia, loperamide, peripheral opioid receptor, tolerance